Infections in children with autism spectrum disorder: Study to Explore Early Development (SEED). Issue 1 (26th November 2018) - Sabourin, Katherine R.; Reynolds, Ann; Schendel, Diana; Rosenberg, Steven; Croen, Lisa A.; Pinto‐Martin, Jennifer A.; Schieve, Laura A.; Newschaffer, Craig; Lee, Li‐Ching; DiGuiseppi, Carolyn
Abstract : Immune system abnormalities have been widely reported among children with autism spectrum disorder (ASD), which may increase the risk of childhood infections. The Study to Explore Early Development (SEED) is a multisite case‐control study of children aged 30–69 months, born in 2003–2006. Cases are children previously diagnosed and newly identified with ASD enrolled from education and clinical settings. Children with a previously diagnosed non‐ASD developmental condition were included in the developmental delay/disorder (DD) control group. The population (POP) control group included children randomly sampled from birth certificates. Clinical illness from infection during the first 28 days ("neonatal, " from medical records) and first three years of life (caregiver report) in cases was compared to DD and POP controls; and between cases with and without regression. Children with ASD had greater odds of neonatal (OR = 1.8; 95%CI: 1.1, 2.9) and early childhood infection (OR = 1.7; 95%CI: 1.5, 1.9) compared to POP children, and greater odds of neonatal infection (OR = 1.5; 95%CI: 1.1, 2.0) compared to DD children. Cases with regression had 1.6 times the odds (95%CI: 1.1, 2.3) of caregiver‐reported infection during the first year of life compared to cases without regression, but neonatal infection risk and overall early childhood infection risk did not differ. Our results support the hypothesis that children with ASD are more likely to have infection early in life compared to the general population and to children with other developmental conditions. Future studies should examine the contributions of different causes, timing, frequency, and severity of infection to ASD risk. Autism Research 2019, 12: 136–146 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: We looked at infections during early childhood in relation to autism spectrum disorder (ASD). We found that children with ASD were more likely to have an infection in the first 28 days of life and before age three compared to children with typical development. Children with ASD were also more likely than children with other developmental delays or disorders to have an infection in the first 28 days of life.